HIGH ALTITUDE VOLLEYBALL PLAYERS THE IMPACT OF RESISTANCE AND AEROBIC TRAINING WITH PROTEIN INTAKE ON BMI - Dr.Adil Rashid Malik (RADJA PUBLIKA, 2023)
This study aimed to investigate the impact of resistance and aerobic training with protein intake on the body mass index (BMI) of volleyball players living at altitude. The participants consisted of 48 male volleyball players, randomly divided into four groups: the resistance training with protein intake group 1 aerobic training with protein intake group II combined resistance and aerobic training with protein intake group III and control group IV the EGunderwent a 12 –week training programme that consisted of resistance and aerobic exercises, coupled with high protein intake . The CG received no intervention during the study period. The BMI of both groups was measured at the beginning and end of the study. The results showed that the EG had a significant decrease in BMI compaired to the CG (p<0.05). The study concludes that resistance and aerobic training with protein intake can effectively reduce BMI in high- altitude volleyball players